2012
DOI: 10.1155/2012/741925
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofBrugmansia arboreaExtract and Its Secondary Metabolites on Morphine Tolerance and Dependence in Mice

Abstract: The aim of the present study was to investigate, in vivo, the effect of a Brugmansia arborea extract (BRU), chromatographic fractions (FA and FNA), and isolated alkaloids on the expression and the acquisition of morphine tolerance and dependence. Substances were acutely (for expression) or repeatedly (for acquisition) administered in mice treated with morphine twice daily for 5 or 6 days, in order to make them tolerant or dependent. Morphine tolerance was assessed using the tail-flick test at 1st and 5th days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…B. arborea extract had an inhibitory effect on the expression of morphine tolerance but no effect on its acquisition. However, B. arborea extract, its fractions, and pure alkaloids reduced significantly both acquisition and expression of morphine dependence (Mattioli et al ., ).…”
Section: Plant Bioactive Componentsmentioning
confidence: 97%
“…B. arborea extract had an inhibitory effect on the expression of morphine tolerance but no effect on its acquisition. However, B. arborea extract, its fractions, and pure alkaloids reduced significantly both acquisition and expression of morphine dependence (Mattioli et al ., ).…”
Section: Plant Bioactive Componentsmentioning
confidence: 97%
“…En otras investigaciones realizadas con el mismo modelo animal se han obtenido diferencias significativas entre el grupo control administrado con agua destilada y los tratamientos administrados con extractos de plantas en diferentes dosis que podría atribuirse a los compuestos químicos que estas poseen (Pérez-Martínez et al, 2020;Guerra et al, 2018;Mejía et al, 2021). También existe un estudio in vivo, donde se reporta el efecto analgésico de algunos alcaloides presentes en esta especie a nivel del sistema nervioso central, además de su potencial terapéutico humano para el tratamiento de la adicción a los opioides (Mattioli et al, 2012). El efecto analgésico estaría mediado por una acción periférica (Cabo de Villa et al, 2020;Pérez et al, 2002), que podría reducir la síntesis de prostaglandinas o interferir en el mecanismo de transducción de los nociceptores primarios aferentes involucrados en este modelo.…”
Section: Resultados Y Discusión Prueba De áCido Acéticounclassified
“…Según Caballero-Serrano et al (2019), B. arborea es ampliamente conocida en la medicina tradicional como una planta mágica, sin embargo agregan usos para tratar distintos dolores. Con base en estudios fitoquímicos (Mattioli et al, 2012;Kim et al, 2020;Algradi et al, 2021) realizados a la especie (Brugmansia arborea) se han encontrado alcaloides tales como: la atropina, hioscina, noratropina (Arteaga de García et al, 1993), hiosciamina y escopolamina (Mattioli et al, 2012), de los que en algunos casos ya se les atribuye una actividad analgésica y antiinflamatoria (Addams & Wang, 2015). Del mismo modo, Kim et al, (2020) determinaron la presencia de flavonoides como kaempferin, kaempferitrin, kaempferol, quercetin, y (+)-aromadendrin; varios de los cuales ya fueron reportados por su efecto antinociceptivo (De Melo et al, 2009, Toker et al, 2004, Almeida-Junior et al, 2020.…”
Section: Introductionunclassified
“…This may be related to the variability of cortisol pulsatility along the day and explain why there is often a weak correspondence between psychophysiological stress and cortisol circulating levels ( 71 ). Other hypotheses, based on preclinical studies ( 72 , 73 ) suggested alterations in serotoninergic and dopaminergic activities. Regarding L-theanine—the main active constituent of green tea—neurochemistry studies have shown potential NMDA receptors modulatory effects, as well as possible increasing effects on brain serotonin, dopamine, and GABA levels ( 74–77 ) that may explain its beneficial effects on the observed outcomes.…”
Section: Discussionmentioning
confidence: 99%